Acute colonic pseudo-obstruction or Ogilvie’s syndrome − A rare complication in the postnatal period: A case report - Urmila Sunda; Renu Makwana; Vinod Shaily; Savi Bhosle; Sushil Choudhary (Journal of Family Medicine and Primary Care)
Ogilvie syndrome, also known as acute colonic pseudo-obstruction, is a form of colonic dilation occurring without underlying mechanical or anatomic etiology. It is a disorder of imbalance in motor innervation of the large intestine, which causes acute colon obstruction in the absence of any physical obstruction. It is associated with high morbidity and mortality due to diagnostic dilemmas and the need for surgical intervention. In gynecological practice, it rarely occurs after a cesarean section. Here, we present a case of Ogilvie syndrome after a cesarean section. The patient developed colonic pseudo-obstruction on the first postoperative day. The patient was managed conservatively using a flatus tube and improved. Ogilvie syndrome should be suspected in a patient with abdominal distension in the postoperative period after ruling out common conditions. Early suspicion and immediate decompression using a flatus tube can improve the outcome of the patient.